Pioglitazone Attenuates Vascular Fibrosis in Spontaneously Hypertensive Rats. (1st April 2012) - Gao, Dengfeng; Ning, Ning; Hao, Guanghua; Niu, Xiaolin
Abstract : Objective . We sought to investigate whether the peroxisome proliferator-activated receptor-γ (PPAR-γ) ligand pioglitazone can attenuate vascular fibrosis in spontaneously hypertensive rats (SHRs) and explore the possible molecular mechanisms. Methods . SHRs (8-week-old males) were randomly divided into 3 groups (n = 8 each) for treatment: pioglitazone (10 mg/kg/day), hydralazine (25 mg/kg/day), or saline. Normal male Wistar Kyoto (WKY) rats (n = 8 ) served as normal controls. Twelve weeks later, we evaluated the effect of pioglitazone on vascular fibrosis by Masson's trichrome and immunohistochemical staining of collagen III and real-time RT-PCR analysis of collagen I, III and fibronectin mRNA.Vascular expression of PPAR-γ and connective tissue growth factor (CTGF) and transforming growth factor-β (TGF-β) expression were evaluated by immunohistochemical staining, western blot analysis, and real-time RT-PCR. Results . Pioglitazone and hydralazine treatment significantly decreased systolic blood pressure in SHRs. Masson's trichrome staining for collagen III and real-time RT-PCR analysis of collagen I, III and fibronectin mRNA indicated that pioglitazone significantly inhibited extracellular matrix production in the aorta. Compared with Wistar Kyoto rats, SHRs showed significantly increased vascular CTGF expression. Pioglitazone treatment significantly increased PPAR-γ expression and inhibited CTGF expression but had no effect on TGF-β expression. Conclusions . The results indicate that pioglitazone attenuated vascular fibrosis in SHRs by inhibiting CTGF expression in a TGF-β-independent mechanism.